Lifestyle factors and comorbidities in gout patients compared to the general population in Western Sweden: results from a questionnaire study. (3rd September 2022) - Dehlin, M; Scheepers, LEJM; Landgren, AJ; Josefsson, L; Svensson, K; Jacobsson, LTH
Abstract : Objective: This study aimed to identify lifestyle factors associated with gout in patients with prevalent gout compared to the general population. Method: Adult patients with gout identified in primary and secondary care in Western Sweden between 2015 and 2017 were sent a questionnaire asking about demographics, lifestyle, and comorbidities. Five age- and gender-matched controls were identified in a random sample of 52 348 individuals aged 16–84 years who participated in the National Public Health survey in Sweden, year 2015. Logistic regression models were used to compare cases and controls with regard to lifestyle factors and comorbidities. Results: Of the 1589 invited gout patients, 868 (55%) responded. After matching for age and gender, 728 were included in the analysis (82.4% male; mean ± sd age 69.3 ± 10.5 years for men and 71.8 ± 9.9 years for women with gout). Male and female gout patients were significantly more likely to be overweight or obese (men 79% vs 66%; women 78.5% vs 65.3%), to have binge-drinking behaviour (men 29.9% vs 11%; women 13.7% vs 2.9%), and to be ex-smokers, compared to controls. Moreover, male gout patients reported lower levels of physical activity, while diabetes and hypertension were more common in both genders with gout than in controls. Conclusion: In this questionnaire study, gout patients reported significantly more obesity and binge-drinking behaviour and less physical activity than controls. This suggests that there are great unmet needs for the management of lifestyle factors, particularly regarding overweight/obesity and binge drinking, in patients with gout.